2021
DOI: 10.1007/s10798-021-09691-5
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: blending spatial skills instruction into a technology teacher preparation programme

Abstract: In recent years, there has been a surge in research in spatial thinking across the international community. We now know that spatial skills are malleable and that they are linked to success across multiple disciplines, most notably Science, Technology, Engineering and Mathematics (STEM). While spatial skills have been examined by cognitive scientists in laboratory environments for decades, current research is examining how these skills can be developed in field-based environments. In this paper, we present fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Virtual reality training has also been used to promote spatial ability in older adults with mild cognitive impairment [34], allocentric space representations in young males [35], as well as spatial visualization and mental rotation in a controlled experiment [12]. The latter study used college-age students (27 females and 22 males, ages [19][20][21][22][23][24][25][26][27][28]. The evidence clearly supports the use of VR training in an effort to enhance spatial visualization ability in first year college students.…”
Section: Virtual Realitymentioning
confidence: 78%
See 1 more Smart Citation
“…Virtual reality training has also been used to promote spatial ability in older adults with mild cognitive impairment [34], allocentric space representations in young males [35], as well as spatial visualization and mental rotation in a controlled experiment [12]. The latter study used college-age students (27 females and 22 males, ages [19][20][21][22][23][24][25][26][27][28]. The evidence clearly supports the use of VR training in an effort to enhance spatial visualization ability in first year college students.…”
Section: Virtual Realitymentioning
confidence: 78%
“…The Purdue Spatial Visualization Test: Rotations (PSVT:R), which involves rotating objects, was selected for this study since it is one of the most widely used spatial visualization tests in the engineering education research community [ 20 , 23 ]. The PSVT:R was designed by Guay in 1976 to determine a “student’s ability to visualize and recognize orthographic drawings” [ 24 ] (p. 161).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Traditional pedagogical approaches prioritize verbal and numerical skills, inadvertently neglecting the potential for enhancing cognitive development through spatial training. In addition, studies indicate a lack of teacher Professional Development for Primary School Teachers Intended to Promote Students' Spatial Ability awareness and understanding of the role of spatial abilities in learning [25,26]. Many educators may not be familiar with the specific strategies and instructional methods that can nurture and cultivate spatial thinking among students.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Yang et al, 2020 conducted a meta-analysis with children aged 0-8 years, which showed that various interventions (such as hands-on exploration, visual prompts, and gestural spatial training), could significantly improve young children's spatial abilities. It is important to note that multiple studies have shown that these interventions sometimes benefit women more than men (Provo et al, 2002;Feng et al, 2007;Sorby et al, 2018;Lane and Sorby, 2022).…”
mentioning
confidence: 99%